A agroecologia e seus espaços de produção acadêmica na UFSCar - Almeida, Adriane Herrmann Corrêa de (Universidade Federal de São Carlos, 2019)
Research in agroecology has grown in the last decades, there has been an increase in the number of undergraduate, technical and postgraduate courses in universities, as well as the creation of research lines in agricultural development centers. The search for alternatives that may respond to the socio-environmental crisis in which we live in is latent. In this sense, the present research aims to describe and analyze the role of scientific research in agroecology at the Federal University of São Carlos (UFSCar). To accomplish this goal, we will present an extensive documental research on the scientific production about agroecology in the mentioned university, interpreting it and showing points of consonances and dissonances. Our method is based on descriptive statistics and semi-structured interviews with prominent researchers. Our main sources of data are the Directory of Research Groups in Brazil and Lattes Platform, both maintained by National Council for Scientific and Technological Development (CNPq). The temporal delimitation of the research covers the period from 1992 to 2018. Among the results and conclusions of the study is the identification that, although research in agroecology is still emerging in UFSCar, it has a strong character of university extension, with networks of researchers establishing themselves beyond the traditional boundaries of academic production.
Agroecology and academic framework at UFSCar
Keywords: Agroecologia; Pesquisa; Grupos de pesquisa; Scientific research; Research groups; UFSCar; Agroecology; CIENCIAS HUMANAS::SOCIOLOGIA::SOCIOLOGIA RURAL